Safety and efficacy of long term asfotase alfa treatment in childhood hypophosphatasia - Debora Mariarita d’Angelo; Federico Lauriola; Luisa Silvestrini; Luigia Cinque; Marco Castori; Giulia Di Donato; Armando Di Ludovico; Saverio La Bella; Francesco Chiarelli; Cosimo Giannini; Luciana Breda (Italian Journal of Pediatrics)
Abstract Background Hypophosphatasia (HPP) is a rare inherited disorder characterized by a deficiency of tissue-non-specific alkaline phosphatase (TNSALP) due to loss-of-function variants of the ALPL gene. HPP is characterized by an extremely variable age of onset and clinical presentation, largely depending on the type of genetic disruption. Childhood HPP commonly presents with skeletal deformities, bone fragility, precocious tooth loss, muscle weakness and sometimes neurological implications. Laboratory tests usually document low levels of alkaline phosphatase (ALP), and radiologic investigations show peculiar bone abnormalities. Treatment with human recombinant TNSALP (asfotase alpha, Strensiq®), available since 2015, is associated with a sudden improvement and a good safety profile. Case presentation A previously healthy 15-month-old girl presented with progressive “genu valgus” and sudden limping. The patient was diagnosed with childhood HPP due to the presence of two ALPL variants, never described in compound heterozygosity: a missense variant c.571G > A, p.(Glu191Lys), and a frameshift deletion c.963delG; p.(Lys322Argfs*44), both classified as pathogenetic. The child was promptly treated with asfotase alpha, and good improvement was quickly obtained. Efficacy, safety, and good tolerance persisted after a long-term follow-up of 6 years. Conclusions Pediatricians should consider HPP in children presenting with a suggestive clinical phenotype. Calcium-phosphorus metabolism, ALP, and vitamin B6 should always be investigated in suspected cases. Moreover, asfotase alfa represents a safe, well-tolerated, and effective drug in children with HPP.